Exploring the nexus between economic growth and economic performance in Nepal - Yadav Mani Upadhyaya; Khom Raj Kharel; Suman Kharel; Basu Dev Lamichhane (Investment Management & Financial Innovations, 2023)
This study aims to explore the relationship between economic growth and performance in Nepal, identifying key drivers for growth. Studying the nexus between economic growth and economic performance in Nepal is crucial for understanding how these factors interact within the nation’s specific context. Growth of gross domestic product (GDP) is represented as the primary indicator for evaluating economic performance, reflecting the overall well-being of a nation's economy. Economic performance encompasses a broader spectrum, including indicators such as employment rate, inflation, income distribution and overall economic stability. Using E-Views 10, a descriptive and analytical research approach has been applied to analyze time series secondary data from 1990–2021 using an econometric model. This study found that faster-growing economies typically experience increased jobs, higher investment, more exports, and often lower inflation. These relationships are part of a long-run equilibrium relationship. In the event of an economic shock disrupting this equilibrium, the economy tends to naturally return to the equilibrium over time. This study found that short-term causality running from lagged GDP, gross capital formation (GCF), exports, human development index (HDI), and employment ratio influence immediate GDP growth. These variables wield a short-term influence over GDP growth; for instance, a sudden surge in exports can prompt a temporary boost in economic growth. This indicates that there is a long-term sustained link between GDP growth and the independent variables rather than merely a short-term event.